PENGARUH MOTIVASI TERHADAP KINERJA OFFICE BOY DI RUANG KERJA KANTOR MPR RI DI MASA WABAH COVID - Zahera Mega Utama (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The title of this research is The Influence of Work Motivation on the Performance of Office Boy employees at the People's Consultative Assembly (MPR RI) office. This study aims: to the performance of Office Boy employees in the office of the People's Consultative Assembly (MPR RI). knowing the effect of work motivation on performance. The method used in this research is descriptive method and the type of correlational study. The approach used in this research is a quantitative approach. In this study, the authors took samples using a non-probability sampling method, which is a method that is not based on a random mechanism in the selection of research samples. The population in this study were Office Boy employees at the People's Consultative Assembly (MPR RI) office, so the number of employees who would be respondents calculated using the Slovin formula amounted to 50 people. The data analysis technique used descriptive analysis and inferential statistical analysis. The conclusion from the results of the analysis that has been carried out, it can be concluded as follows: 1. The regression model in the coefficients table shows that the value of the motivation variable (X) is X = 000 is smaller than 005. These results conclude that the regression model has a significant effect on the performance variable (Y).2. The coefficient value of the recruitment path on performance is 0.628 with a t-value of 9.151. Because the value of tcount is greater than the value of ttable at dk = 18 for = 0.05 of 0.158, then H0 is rejected and H1 is accepted, which means that there is a direct positive effect of the motivational variable on the performance variable.